Science, Migration, and Our Ever More Global Society - Phillips, Clarence Mark (European Scientific Journal, ESJ, 2016)
Nation states once contained distinct groups of people based on a common heritage, language, religion, or ethnicity. Today, the nation state is largely a political and economic entity. In the past, migration from one part of the world to another occurred only rarely, and usually on an individual basis. Now, mass migrations are becoming more frequent, and for a greater number of reasons. While genocide and ethnic cleansing are nothing new, migrations now occur (and are expected to occur more often in the future) for political, economic, and environmental reasons as well. Natural disasters â€“ like earthquakes and droughts â€“ as well as those intensified by human behavior â€“ such as resource depletion or rising sea levels â€“ will only exacerbate the likelihood of mass migration. The need for large groups of people to move from one part of the planet to another has never been greater, and yet their ability to do so is still seriously hindered by national divisions. Of course, cooperation among nations has grown enormously since the end of the Second World War, but mass migrations like the recent crisis faced by refugees from Syria show that division based on national distinction is preventing our common humanitarian efforts. The argument put forth in this paper is that the nation state (along with the fighting it engenders) has outlived its usefulness, and now hinders human progress more than helps it. Here the scientific community is seen as a model for cooperation across national frontiers, showing that the goal of â€œpeople without bordersâ€ (les Ãªtre humains sans frontiÃ¨res) is not only attainable, but is itself a necessary means toward greater human achievement in the future. For scientists are themselves merely people who base their decisions on empirical findings and group consensus â€“ and their international cooperation is a model which the rest of the world would do well to emulate.